The State of Technology Innovation in Nigeria: Trends, Challenges and Opportunities - Bansal, Pratik (Journal of Marketing Studies, 2024)
Purpose: This writeup examines the state of technology innovation in Nigeria, focusing on emerging trends, prevalent challenges, and untapped opportunities. Methodology: By analyzing current trends, identifying key challenges, and exploring potential opportunities. Findings: As Africa's largest economy and most populous country, Nigeria has shown significant potential for technological advancement and innovation. However, various factors, including infrastructure limitations, funding constraints, and regulatory barriers, have posed challenges to the growth of the technology sector. Unique Contribution to Theory, Practice and Policy: This study aims to provide insights into the landscape of technology innovation in Nigeria and offer recommendations for fostering its development.